Mathematically Creative Thinking Abilities Students of Elementary School on Learning Inquiry Training Based on Learningstyle - Fathoni, Isna Muhammad; Isnarto, Isnarto; Haryani, Sri (Journal of Primary Education, 2018)
Elementary school students need to be taught mathematics to equip logical, analytical, systematic, critical, creative, and cooperative thinking skills. Result of the UNESCO 2016 survey found that the creative thinking ability of students in elementary education level in Indonesia is low. This study has two purposes. First, to analyze the effectiveness of the inquiry training model on the mathematical learning material counting integer operations. Second, to analyze the creative thinking ability of 5th grade students based on learning style. Mixed methods with concurrent triangulation strategy was carried out in 5B grade Islamic Elementary School Al Madina Semarang with the number of students are 29. The next step is selected the subject of research is 6 students by purposive sampling. The data analysis technique used is the assisted appeal SPSS 16.00. Data validity technique through qualitative method of verification and source triangulation. The results show that model inquiry training is effective at learning mathematics class 5B. This model is effective by fulfilling three conditions. First, the percentage of mastery in the model inquiry training class reached 86%. Second, the average ability of mathematical thinking in the class of inquiry training is higher than the average in mind mapping class. The mean of inquiry training is 81.61 and mind mapping is 76.35. Third, the implementation of inquiry training activities including good category. Students with kinesthetic learning styles included in the category of students are creative and creative enough. Students with visual learning styles included in the category of students are less creative and not creative. Students with auditory learning styles included in the category of creative and highly creative students. This research is useful to enrich the sense of insight of the application of inquiry training model and know the classification of students' mathematical creative thinking ability based on the learning style.